Social security as a subject of human geography research study - Niemets, L.; Niemets, K.; Segida, K.; Sokolenko, A. (Paris: “Paris University Press”, 2014)
This article deals social security as a subject of human geography research study. The publication focuses on the social, economic, geoecological, information, mental and cultural components of social development of Ukraine. The main social problems and scientific aspects of social security in Ukraine are considered
Keywords: social security; social; economic; geoecological; information; mental and cultural components of a sociogeoprocess; Ukraine